Endowments, power, and democracy: Political economy of multilateral commitments on trade in services - Martin Roy (World Trade Organization (WTO), 2010)
In spite of their growing importance in international trade as well as in bilateral and multilateral trade negotiations, services have only attracted limited attention from researchers interested in determinants of trade policies and trade cooperation. This paper seeks to account for countries' varying levels of market access commitments under the multilateral General Agreement on Trade in Services (GATS). I develop an argument suggesting how levels of democracy and factor endowments are associated with more commitments. The empirical analysis supports these propositions, and also suggests that relative size, as well as regulatory capacity, are positively linked to GATS commitments.
Keywords: F5; F13; L8; D72; 330; trade in services; GATS; democracy; relative power; endowments; WTO accessions; determinants of cooperation; determinants of international commitments; international negotiations; Internationaler Dienstleistungsverkehr; GATS; Welt